Ray tracing user interface of metamaterial-based complex-shaped optical elements - Hao, Mingyu (Nanyang Technological University, 2024)
This final project report describes an innovative ray tracing user interface designed for the interactive exploration of complex shaped optical elements based on objects with adjustable refractive index and metamaterials. Developed using HTML, CSS, and JavaScript, and making extensive use of the p5.js library, this web-based tool provides a dynamic platform for visualizing and manipulating the behavior of light in the presence of a variety of optical phenomena, including reflection and refraction. The main goal of the project is to fill a significant gap in accessible, intuitive platforms that allow real-time experiments on light interactions on different media, with a particular focus on materials with negative refractive indices (metamaterials). The user interface facilitates hands-on learning by enabling users to adjust the refractive index of an object so that they can observe the instantaneous effects on the optical path. The simulation supports a range of light sources and optical components, providing customizable properties to simulate different scenarios. Performance evaluations show that simulated optical interactions are of high fidelity and optimization ensures smooth operation across devices. Feedback emphasized the effectiveness of the tool in enhancing optics education, making complex principles accessible through interactive exploration. Going forward, features that can be advanced include extending the range of optical components, integrating advanced metamaterials simulations, and improving mobile accessibility, thus expanding the tool's educational and research applicability.